The Efforts to Improve The Learning Outcome of Front Rolling Floor Gymnastics through a Problem-Based Learning Models - Ghashya Galih Prihatna; Dini Rosdiani; Yudi Hidayat (Journal of Physical and Outdoor Education, 2026)
The purpose of this study is to find out whether there is an increase in students' skills in performing the front roll movement model after the application of Problem Based Learning to improve student learning outcomes in learning front roll floor gymnastics at the elementary school (SD) level. To find out that Problem Based Learning has a better impact than conventional lecture-based learning. The method in this study is quasi-experimental with a pretest-posttest control group design model. Based on the results of data analysis, it was shown that the learning results of the gymnastics floor in front of the experimental class with the Problem Based Learning learning model obtained an average score of 79.5 with the highest score of 94 and the lowest score of 63, while the control class with the conventional model had an average score of 66.6 with the highest score of 81 and the lowest score of 50. Therefore, it can be concluded that the use of the Problem Based Learning learning model significantly increased the learning outcomes of front floor gymnastics compared to the conventional learning model in grade V students of Citeureup Mandiri State Elementary School 1.